The "more economic approach" in EU merger control: A critical assessment - Arndt Christiansen (Deutsche Bank Research, 2006)
With the "more economic approach" the EU is taking a new tack on merger control policy. This is visible not only in the new SIEC prohibition criterion and the criteria for appraising horizontal mergers but also in more recent decision-making practice. Greater legal certainty, on the one hand, and improved decision-making, on the other, have been cited as the aims of the (increased) use of industrial economics models and quantitative analysis. The objective of a (better) economic foundation in EU merger control is expressly welcomed. However, on closer analysis it is found that in point of fact the more economic approach in its present form creates less legal certainty, while the upshot in terms of the quality of the decision-making is at least unclear. At the same time, the (administrative) burden is likely to rise. Moreover, certain problems emerge for instance from the increasing involvement of economic experts or the possibilities for (industrial policy-related) political intervention. In conclusion, a broader perception of an economics-based approach which takes account especially of the institutional implications is called for. Specific recommendations are the establishment of an independent competition authority and the stronger orientation of merger control to (more) general rules.
Keywords: F02; K21; L40; 330; Competition policy; EU merger control; economic analysis; Fusionskontrolle; EU-Wirtschaftsrecht; Industrieökonomik; Kritik; EU-Staaten